Physical activity, fatness, educational level and snuff consumption as determinants of semen quality: findings of the ActiART study. Issue 1 (July 2015) - Pärn, Triin; Grau Ruiz, Raúl; Kunovac Kallak, Theodora; Ruiz, Jonatan R.; Davey, Eva; Hreinsson, Julius; Wånggren, Kjell; Salumets, Andres; Sjöström, Michael; Stavreus-Evers, Anneli; Ortega, Francisco B.; Altmäe, Signe
Abstract In this study, the association between physical activity and other potential determinants, objectively measured by accelerometry, was examined. Sixty-two men attending an infertility clinic participated in the study. Obese men (body mass index ≥ 30) and those with a waist circumference 102 cm or more had lower semen volume than the other men (P < 0.05). Higher values in sperm parameters were observed in participants who completed university studies and those who did not consume snuff, compared with the other participants (P < 0.05). Finally, men who spent an average number of 10 min-bouts of moderate-to-vigorous physical activity had significantly better semen quality than those who engaged in low or high numbers of bouts of activity (P < 0.05). No associations were found for sedentary or moderate-to-vigorous physical activity time when it was not sustained over 10 min, i.e. not in bouts. Men who have average levels of physical activity over sustained periods of 10 min are likely to have better semen quality than men who engage in low or high levels of such activity. Similarly, high levels of total and central adiposity, low educational level and snuff consumption are negatively related to semen quality.